EFFECTOR OF TRANSCRIPTION factors are novel plant‐specific regulators associated with genomic DNA methylation in Arabidopsis. Issue 1 (25th September 2018) - Tedeschi, Francesca; Rizzo, Paride; Huong, Bui Thi Mai; Czihal, Andreas; Rutten, Twan; Altschmied, Lothar; Scharfenberg, Sarah; Grosse, Ivo; Becker, Claude; Weigel, Detlef; Bäumlein, Helmut; Kuhlmann, Markus
Summary: Plant‐specific EFFECTORS OF TRANSCRIPTION (ET) are characterised by a variable number of highly conserved ET repeats, which are involved in zinc and DNA binding. In addition, ETs share a GIY‐YIG domain, involved in DNA nicking activity. It was hypothesised that ETs might act as epigenetic regulators. Here, methylome, transcriptome and phenotypic analyses were performed to investigate the role of ET factors and their involvement in DNA methylation in Arabidopsis thaliana . Comparative DNA methylation and transcriptome analyses in flowers and seedlings of et mutants revealed ET‐specific differentially expressed genes and mostly independently characteristic, ET‐specific differentially methylated regions. Loss of ET function results in pleiotropic developmental defects. The accumulation of cyclobutane pyrimidine dimers after ultraviolet stress in et mutants suggests an ET function in DNA repair.